A study of its incidence, risk factors, laboratory parameters and outcome in patients with acute kidney injury and acute decompensated heart failure - Khalid Mehdi; Bilal Bin Abdullah; Nida Nausheen (Al Ameen Medical College, 2019)
Background: The burden of HF in India appears high and acute kidney injury is a leading cause of morbidity and mortality. The mechanisms underlying this interaction are complex and multifactorial in nature. Objective: To know the incidence, risk factors, laboratory parameters and outcome of such patients. Methods: A sample size of 100 cases of admitted to Intensive Care Unit in Al Ameen Medical College Hospital in age group between 20 to 80 years. The study period was December 2016-June2018. Results: In this study the mean age is 55.3±12.8 years and majority of patients were male (74%). Conclusion: The male predominance, age group 40-50 and 50-60, prompt diagnosis and management reduces morbidity and mortality.